Deformation - strength parameters of arteries of the brain in the ii period of mature age - V. N. Nikolenko; O. A. Fomkina (Сеченовский вестник, 2019)
The aim of research - to identify the features of the biomechanical parameters of the arteries of the brain in the II period of adulthood. Materials and methods. The samples of anterior (ACA), middle (MCA), posterior cerebral (PCA), posterior connective (PCoA), basilar arteries (BA) and intracranial parts of vertebral arteries (VA) seized at autopsy of 40 corpses of men andwomen aged 35-60 years were studied. In the longitudinal tension experiment on the tensile testing machine Tira Test studied the overall strength, tensile strength, maximum relative deformation and young's modulus of walls.Results. The paper describes the average values and variability parameters of the studied biomechanical parameters of arteries. The results of the comparative analysis with the average values typical for the population of adults aged 21-90 years are presented. Conclusion. Biomechanical properties of cerebral arteries are characterized by signiﬁcant variability. The least changeable is the overall strength of the artery wall. The data obtained diﬀer from the average values typical for the population of adults aged 21-90 years. The greatest diﬀerences were found for the ultimate strength of the vascular wall. In the II period of adulthood, this parameter in MCA, PCA, BA, ACA and BA is 8-15% more, and in PCoA is 22% less than the average value.